THE Correlation Between Prior Knowledge and Skimming Ability in Reading Comprehension of Second Semester Students of English Language Teaching Department at STAIN Jurai Siwo Metro - M. Sayid Wijaya (Jurnal Pedagogy, 2014)
Prior knowledge is believed to be one of the factors related to students’ reading comprehension. In reading, a student brings their experience about the topic to the act of reading to ease them comprehend the text. In this case, selection of reading techniques is very crucial. Among reading technique which depends on prior knowledge is skimming. When students are to skim the text, their prior knowledge will help them catch the gist of the text easily because they are familiar with the topic of the text.Therefore, this research tried to investigate the correlation between prior knowledge and skimming ability in reading comprehension.